2020
DOI: 10.1371/journal.pone.0243837
|View full text |Cite
|
Sign up to set email alerts
|

Novel Honokiol-eluting PLGA-based scaffold effectively restricts the growth of renal cancer cells

Abstract: Renal Cell Carcinoma (RCC) often becomes resistant to targeted therapies, and in addition, dose-dependent toxicities limit the effectiveness of therapeutic agents. Therefore, identifying novel drug delivery approaches to achieve optimal dosing of therapeutic agents can be beneficial in managing toxicities and to attain optimal therapeutic effects. Previously, we have demonstrated that Honokiol, a natural compound with potent anti-tumorigenic and anti-inflammatory effects, can induce cancer cell apoptosis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Compared with synthetic drugs, treatment with natural products have fewer side effects, while exhibiting favorable outcomes ( 13 ). Although other studies have reported that several natural products, such as Epigallocatechin Gallate ( 19 ), quercetin ( 20 ), englerin A ( 21 ), honokiol ( 22 ), curcumin ( 23 ) and resveratrol ( 24 ) have shown beneficial results in preclinical studies of RCC, the research on the mechanism of the therapeutic activities of natural products on RCC is remains limited. The present study examined the antitumor effects of natural products on RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with synthetic drugs, treatment with natural products have fewer side effects, while exhibiting favorable outcomes ( 13 ). Although other studies have reported that several natural products, such as Epigallocatechin Gallate ( 19 ), quercetin ( 20 ), englerin A ( 21 ), honokiol ( 22 ), curcumin ( 23 ) and resveratrol ( 24 ) have shown beneficial results in preclinical studies of RCC, the research on the mechanism of the therapeutic activities of natural products on RCC is remains limited. The present study examined the antitumor effects of natural products on RCC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Hamedani et al, in their work, presented an innovative PLGA-based electrospun polymer fiber scaffold for renal cell carcinoma (RCC). The scaffold was loaded with a natural compound showing a strong anticancer and anti-inflammatory effect, which is Honokiol, which showed an inhibitory effect on the proliferation and migration of kidney cancer cells [ 152 ]. In turn, Zheng et al, in the latest research, presented the 3D scaffold HA15 bone tissue, printed in 3D β-TCP/PLGA technology with the drug promoting osteogenesis HA15 in in vivo studies in rabbits.…”
Section: Synthetic Matricesmentioning
confidence: 99%
“…In vivo and in vitro studies have also demonstrated anti-tumour effects of honokiol in a variety of cancers, including those of brain, blood, bone, skin, lung, colon, pancreas, breast, and prostate [4]. Specifically, honokiol activates cell cycle arrest and apoptosis, as well as inhibits proteins that promote cancer growth [4,5]. However, two connected phenyl rings in the chemical structure of honokiol cause its poor water solubility and limited bioavailability as well as instability due to the possibility of hydrolysis and oxidation [1,6].…”
Section: Introductionmentioning
confidence: 99%